Skeletal Anatomy of Acaenasuchus Geoffreyi Long and Murry, 1995 (Archosauria: Pseudosuchia) and its Implications for the Origin of the Aetosaurian Carapace. Issue 4 (3rd July 2020) - Marsh, Adam D.; Smith, Matthew E.; Parker, William G.; Irmis, Randall B.; Kligman, Ben T.
ABSTRACT: Acaenasuchus geoffreyi is a diminutive armored archosaur from the Upper Triassic Chinle Formation of northern Arizona, U.S.A., with uncertain evolutionary relationships and skeletal maturity. Known only from osteoderms, the taxon has been considered a valid taxon of aetosaur, juvenile specimens synonymous with the aetosaur Desmatosuchus spurensis, or a non-aetosaurian pseudosuchian archosaur. Here, we describe new fossils of Acaenasuchus geoffreyi that represent cranial, vertebral, and appendicular elements as well as previously unknown variations in the dorsal carapace and ventral shield. The skull bones are ornamented with the same anastomosing complex of ridges and grooves found on the paramedian and lateral osteoderms, and the appendicular skeleton resembles that of Revueltosaurus callenderi, Euscolosuchus olseni, aetosaurs, and other armored archosaurs such as erpetosuchids. Histology of osteoderms from the hypodigm of Acaenasuchus geoffreyi shows multiple growth lines, laminar tissue, and low vascularity, evidence that the individuals were close to skeletal maturity and not young juveniles. A revised phylogenetic analysis of early archosaurs recovers Acaenasuchus geoffreyi and Euscolosuchus olseni as sister taxa and members of a new clade that is the sister taxon of Aetosauria. This new phylogeny depicts a broader distribution of osteoderm character states previously thought to only occur in aetosaurs, demonstrating the danger of using only armor character states in aetosaur taxonomy and phylogeny. Acaenasuchus geoffreyi is also a good example of how new fossils can stabilize 'wild card' taxa in phylogenetic analyses and contributes to our understanding of the evolution of the aetosaur carapace.